STUDENTS’ PERCEPTIONS OF THE IMPLEMENTATION OF ICT-BASED BLENDED LEARNING FOR ENGLISH GRAMMAR CLASS. - Lastari, Dyah Supraba; Rohim, Abdul (TELL - US JOURNAL, 2023)
During the transition period following the pandemic Covid19, the use of ICT (information and communication technology) has significantly impacted the teaching and learning processes in EFL classes. Since the implementation of “new normal”, many educational institutions have started to implement blended learning. Utilizing technology has been considered as an essential solution to allow blended-learning possible in various fields of subjects, including English grammar. This research was aimed to investigate students’ perspective on the ICT utilization for blended learning of English grammar. The subjects of this research were third semester students at Muhammadiyah University of Tangerang. Researchers used questionnaires and interviews to collect data on how they perceive technology integration in blended learning to facilitate them study English grammar.  The participants experienced blended learning by using LMS (Learning Management System); video conferencing platform; video sharing website; social media and game-based application.   The findings showed that students’ perception of the use of technology for learning grammar in blended learning indicated positive results